Potent antitumor efficacy of anti-GD2 CAR T cells in H3-K27M+ diffuse midline gliomas. (May 2018) - Mount, Christopher; Majzner, Robbie; Sundaresh, Shree; Arnold, Evan; Kadapakkam, Meena; Haile, Samuel; Labanieh, Louai; Hulleman, Esther; Woo, Pamelyn; Rietberg, Skyler; Vogel, Hannes; Monje, Michelle; et al.
Abstract Diffuse intrinsic pontine glioma (DIPG) and other diffuse midline gliomas (DMGs) with mutated histone H3 K27M (H3-K27M)1–5 are aggressive and universally fatal pediatric brain cancers6 . Chimeric antigen receptor (CAR)-expressing T cells have mediated impressive clinical activity in B cell malignancies7–10, and recent results suggest benefit in central nervous system malignancies11–13 . Here, we report that patient-derived H3-K27M-mutant glioma cell cultures exhibit uniform, high expression of the disialoganglioside GD2. Anti-GD2 CAR T cells incorporating a 4-1BBz costimulatory domain14 demonstrated robust antigen-dependent cytokine generation and killing of DMG cells in vitro. In five independent patient-derived H3-K27M+ DMG orthotopic xenograft models, systemic administration of GD2-targeted CAR T cells cleared engrafted tumors except for a small number of residual GD2lo glioma cells. To date, GD2-targeted CAR T cells have been well tolerated in clinical trials15–17 . Although GD2-targeted CAR T cell administration was tolerated in the majority of mice bearing orthotopic xenografts, peritumoral neuroinflammation during the acute phase of antitumor activity resulted in hydrocephalus that was lethal in a fraction of animals. Given the precarious neuroanatomical location of midline gliomas, careful monitoring and aggressive neurointensive care management will be required for human translation. With a cautious multidisciplinary clinical approach, GD2-targeted CAR T cell therapy for H3-K27M+ diffuse gliomas of pons, thalamus and spinal cord could prove transformative for these lethal childhood cancers. Lethal pediatric tumors bearing a particular histone H3 mutation upregulate the disialoganglioside GD2, thereby making these tumors susceptible to chimeric antigen receptor T cell–based immunotherapy.